THE IMPORTANCE OF WORLD CHILDREN'S LITERATURE IN EDUCATION - Jurayeva Sevara Kakhraman qizi (Scholars Digest Publishing, 2023)
The article annotation explores the significance of world children's literature in education, highlighting its role in promoting cultural understanding, fostering empathy, and enhancing language and literacy skills. It emphasizes the importance of exposing children to diverse perspectives and experiences through literature, and how it contributes to their overall development and global awareness.
Keywords: breaking down stereotypes, promoting cross-cultural understanding, safe space, multicultural education, cultural awareness.